Diagnosis and surgical treatment of extrahepatic portal vein aneurysm: A case report. (October 2015) - He, Hao; Antonopoulos, Constantine N; Moulakakis, Konstantinos G; Sfyroeras, George S; Kakisis, John D; Papapetrou, Anastasios; Smyrniotis, Vasilios; Liapis, Christos D
Extrahepatic portal vein aneurysm is a relatively uncommon entity. We reported the case of a 51-year-old man, who was incidentally diagnosed with an asymptomatic 52 × 65 mm portal vein aneurysm, which was located at the main trunk of the portal vein, just before its bifurcation. The patient was treated with partial clamping of the portal vein aneurysm and aneurysmorrhaphy. Postoperative course was uneventful. Surgical intervention should be considered for patients with large, symptomatic or expanding portal vein aneurysms.